The internationalization dilemma [recurso electrónico] (2011)
For the last decades, firms have increasingly tried to grow though expanding themselves to global markets. Globalization gives access to foreign markets and different kinds of resources. However, foreign internationalization -defined as the procesess in wh-+ich firms increasingly move farther from the home country (Barkema & Bell, 1996)- has several hazards too. When a firm decides to penetrate international markets, it has to deal with uncertainty. This means, going beyond national borders which impies dealing with uncertainty and risk. The first question that the firm has to face is: which is the target country for internationalization?